Size, heterogeneity and distributional effects of self-employment income tax evasion in Italy - Martina Bazzoli; Paolo Di Caro; Francesco Figari; Carlo V. Fiorio; Marco Manzo (University of Essex, Institute for Social and Economic Research (ISER), 2020)
We measure tax evasion in Italy by estimating a food expenditure equation that disentangles households with prevalent income from self-employment, which is self-declared, from those with mostly third-party reported income. By using a novel dataset that links the 2013 Italian Household Budget Survey with individual tax records over a period of 7 years, we reduce measurement error by a great extent. We also depart from the usual constant share of underreporting, showing that underreporting heterogeneity among self-employed is significant, and is larger for singles and for college-educated households. We show that self-employed workers in Italy exhibit a similar attitude to tax evasion as those in other developed countries. Therefore, we point to the structure of the economy for an explanation of why aggregate tax evasion in Italy is larger than in other developed countries. The estimated heterogeneity of underreporting behavior of households combined with the use of a tax-benefit microsimulation model have allowed us to shed light on the distributional effects of income tax evasion, showing that almost 73% of the missing revenue is attributable to tax-payers at the top of the income distribution.
Keywords: H26; H31; D31; 330; tax evasion; administrative data; distributional effects; food expenditure; Italy